EFFECT OF BALANCE TRAINING ON DYNAMIC POSTURAL CONTROL IN SUBJECTS WITH CHRONIC ANKLE INSTABILITY. Issue 7 (11th March 2014) - De Ridder, R; Willems, T; Vanrenterghem, J; Roosen, P
Abstract : Background: Chronic ankle instability (CAI) is a frequently reported residual outcome after an acute ankle sprain. Balance training is common daily practice in treatment of CAI, but its effect on CAI associated mechanisms as postural control remains unclear. Objective: The aim of this study was to establish the presence of postural deficits in subjects with CAI and assess the effect of an 8-week balance training program on dynamic postural control. Design: Case-control baseline group characteristics were determined and intervention effects were evaluated. Setting: All subjects were tested in a laboratory setting and the intervention group performed a home-based balance protocol. Participants: Data were collected for 74 recreationally active subjects (43 subjects with CAI and 31 controls). Interventions: Subjects with CAI performed an 8-week progressive, home-based balance protocol. Subjects had to perform these balance exercises 3 times a week. Eighteen subjects with CAI first served as control group without intervention, before entering the balance program. Main outcome measurements: Postural control was quantified by means of the dynamic postural stability index (DPSI) and its separate directional stability indices (mediolateral, anterior/posterior and vertical). Perceptual outcomes were documented using the FADI and FADI-Sport. Results: At baseline, subjects with CAI displayed higher anterior/posterior (P=.002) and vertical postural instability (P=.001), a poorer DPSI (P<.001), and lower subjective stability scores (FADI and FADI-Sport, P<.001) compared to the control group. After balance training, stability scores improved significantly (FADI p=0.001, FADI-Sport P=.005), although no changes were noted for the stability indices. Conclusion: Subjects with CAI have an impaired postural control. As a treatment modality, balance training exhibits its capability of improving the subjective feeling of instability in subjects with CAI. However, there was no effect on dynamic postural control measured by DPSI.